2009
DOI: 10.1021/bi9013962
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Kinetics of the GroEL−gp31 Chaperonin Complex Studied with Förster Resonance Energy Transfer

Abstract: Propagation of bacteriophage T4 in its host Escherichia coli involves the folding of the major capsid protein gp23, which is facilitated by a hybrid chaperone complex consisting of the bacterial chaperonin GroEL and the phage-encoded co-chaperonin, gp31. It has been well established that the GroEL-gp31 complex is capable of folding gp23 whereas the homologous GroEL-GroES complex cannot perform this function. To assess whether this is a consequence of differences in the interactions of the proteins within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Binding of gp23 to the GroEL folding cage shows features distinct from those of most bound E. coli proteins. However, it has been shown that gp23 is able to interact with the GroEL–GroES complex, although not productively (Calmat et al ., 2009). Unlike substrates such as RUBISCO, gp23 occupies both chambers of the GroEL folding cage, and only gp31 is able to promote efficient capped single “ cis ” chamber folding, apparently by creating a larger folding chamber (Clare et al ., 2009).…”
Section: Structure and Assembly Of Phage T4 Capsidmentioning
confidence: 99%
“…Binding of gp23 to the GroEL folding cage shows features distinct from those of most bound E. coli proteins. However, it has been shown that gp23 is able to interact with the GroEL–GroES complex, although not productively (Calmat et al ., 2009). Unlike substrates such as RUBISCO, gp23 occupies both chambers of the GroEL folding cage, and only gp31 is able to promote efficient capped single “ cis ” chamber folding, apparently by creating a larger folding chamber (Clare et al ., 2009).…”
Section: Structure and Assembly Of Phage T4 Capsidmentioning
confidence: 99%
“…As was known before [26], the major head protein gp23 requires assistance of the phage-encoded chaperonin gp31 that is a functional analogue of bacterial GroES protein able to functionally replace it in interaction with the cellular chaperonin GroEL [27]. However, in our experiments this protein was also produced in native conformation using low temperature expression in presence of Cpn10 and Cpn60 chaperones derived from Oleispira antarctica showing 74 and 54% amino acid identity with groEL and groES of E. coli (Agilent Technologies, ArcticExpress Specification).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experiments this protein was also produced in native conformation using low temperature expression in presence of Cpn10 and Cpn60 chaperones derived from Oleispira antarctica showing 74 and 54% amino acid identity with groEL and groES of E. coli (Agilent Technologies, ArcticExpress Specification). Recently, the ability of groEL-groES complex to interact with gp23 was reported [27]. Low temperature expression without chaperones yielded an insoluble product, which leads to the suggestion that Cpn10–Cpn60 complex may possess some feature(s) of GroEL-gp31 complex or groEL–groES complex (possibly the size of internal cavity of the chaperonin) allowing it to assist gp23 folding in T4 infected cells.…”
Section: Discussionmentioning
confidence: 99%